Conhecimento escolar em ciências naturais no ensino fundamental - Gallian, Claudia Valentina Assumpção (2005)
This research intended to characterize the school knowledge of science through observation and research into two teachers classes in the 5th and 7th grades in a public school in Campinas, São Paulo. The theoretical contributions related to the school, the accumulation of practice, the process of constitution of school knowledge on the scientific bases, give support to the analyses presented on this research and have the following authors as the main references: J. Gimeno Sacristán; Jean-Pierre Astolfi and Michel Develay; Guy Vincent, Bernard Lahire and Daniel Thin; Lucíola L. C. P. Santos; Alice Ribeiro C. Lopes and Júlia Varela. Throughout the text, the description and analysis of the teachers actions can be found with the aim of showing the facts that guide, make easier and/or limit the teachers choices related to the contents and to the way of dealing with the knowledge related to the sciences and the impact of these choices on the quality of the students approximation to the scientific bases. One of the actions observed reproduced the standard already related in other researches about the teaching of science, the fragment and the simplicity of knowledge and that the teaching process was centred on the teacher and the textbook. The other one showed more emphasis on the development of the students autonomy and the knowledge from other sources out of school. However, blanks and restrictions on the process of natural sciences knowledge can be found in both of the situations observed because of the limits of the school system. Thus, the school knowledge shows its characteristics and particularity